The Importance Of Teaching Literature To Students - Maharsi, Ista (Journal of English and Education (JEE), 2012)
Literature, in its own self, possesses rich heritage, social, political, philosophical, and economical reflection of an era. It has long been used to depict various circumstances, sound social critiques on a particular condition, reflect characteristics of an age, portray culture of a society, and reveal conspiracy in a country. Literature is widely learned and discussed in schools, yet its benefits and values are often questioned. This paper is aimed to elaborate the idea of the necessity of teaching literature to students and how it can be bought into classrooms.Key words: literature, language, values, students